2005
DOI: 10.1007/s11249-004-1775-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lubrication and humidity on the abrasiveness of a thin boron carbide coating

Abstract: Studies using thin boron carbide (B 4 C) coatings have previously been performed in order to investigate their potential use as finite-life run-in coatings. Such coatings have been shown to polish the mating surface in a relatively short time. The inherent ability of these coatings to polish can potentially allow them to function as finite-life run-in coatings. Employing such coatings requires a thorough understanding of the parameters which directly influence the changes that occur in the coating abrasiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Although the absence of boric acid prevents further friction reduction in this system, B-O compounds could provide low friction coefficient (around 0.11) in boundary lubrication conditions. The above results are in agreement with the previous report by Siniawski et al [27] which suggested that an evolution of the surface oxidation of the B 4 C coating primarily lead to the reduction in friction coefficient. In terms of wear performance of the Steel/B 4 C system, a large amount of phosphorus which generally plays a significant role as an anti-wear agent at the rubbing surface was detected on the wear scar of the ball in Oil B compared to that in Oil A.…”
Section: Steel/b 4 C Tribocouples With Oil a And Bsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the absence of boric acid prevents further friction reduction in this system, B-O compounds could provide low friction coefficient (around 0.11) in boundary lubrication conditions. The above results are in agreement with the previous report by Siniawski et al [27] which suggested that an evolution of the surface oxidation of the B 4 C coating primarily lead to the reduction in friction coefficient. In terms of wear performance of the Steel/B 4 C system, a large amount of phosphorus which generally plays a significant role as an anti-wear agent at the rubbing surface was detected on the wear scar of the ball in Oil B compared to that in Oil A.…”
Section: Steel/b 4 C Tribocouples With Oil a And Bsupporting
confidence: 93%
“…In-situ Raman analysis revealed the formation of boric acid and carbon at the sliding interface of annealed B 4 C and sapphire and evolution of carbon amount lead to higher friction [26]. In terms of the tribological properties of lubricated B 4 C, Siniawski et al [27] reported that B 4 C coatings lubricated with mineral oil in boundary lubrication condition showed low friction coefficient: around 0.12 compared with unlubricated B 4 C. However, the interaction between B 4 C contact surface and lubricant additives is not fully understood.…”
Section: B 4 C Tribological Performance In Different Environmentsmentioning
confidence: 99%
“…It was found by Siniawski et al [10][11][12][13] that the average abrasiveness decreased with increasing sliding distance following the power law as…”
Section: Resukts and Discussionmentioning
confidence: 95%